Variation of the diet of the sea urchin (Diadema mexicanum (Diadematoida: Diadematidae)) according to its size in the Eastern Tropical Pacific - Bogantes-Retana, Andrea (2024)
Introduction: The sea urchin Diadema mexicanum, due to its bioerosion activity, is considered of ecological importance. This phenomenon could negatively or positively affect coral reef ecosystems. The bioerosion process varies according to the abundance and size of the sea urchin. Objective: Juvenile organisms possess different metabolic needs compared to adults, so knowing their stomach content according to size allows us to quantify the selection of substrate bioeroded. Methods: To determine this, D. mexicanum individuals were collected in 12 sites from January 2009 to September 2010 along the Eastern Tropical Pacific coast. The stomach content was categorized in Carbonated Fraction (CF), Non-Carbonated Fraction (NCF), and Organic Matter (OM). Stomach content was analyzed according to a) juvenile (< 2.5 cm) or adult (> 2.5 cm) stage and b) locality. Results: Juveniles presented the following stomach content average percentages: 20.7 % OM, 12 % NCF and 67.9 % CF; and adults: 11.4 % OM, 14.8 % NCF and 73.8 % CF. Based on a Wilcoxon test and a Kendall linear regression, the following results were obtained. The carbonated fraction in the stomach increased by 0.47 units on average for every cm of growth (p < 0.05). OM consumed by D. mexicanum increases only 0.05 units for every cm of growth (p < 0.05). We found a difference of stomach content depending on the site (p < 0.05) and life stage (p < 0.05). Localities like Huatulco and Coco presented significant differences that could be related to local oceanographic conditions. Conclusions: We relate these changes of the stomach fractions to the necessity of the juvenile sea urchins for nutrients to maintain their growth. The amount of OM is crucial for the development of early stages, meaning that there is a difference in substrate selection associated with growth.